2021
DOI: 10.3389/fimmu.2020.604591
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence Study of T Cells: A Systematic Review

Abstract: BackgroundAging is accompanied by alterations in immune response which leads to increased susceptibility to infectious diseases, cancer, autoimmunity, and inflammatory disorders. This decline in immune function is termed as immunosenescence; however, the mechanisms are not fully elucidated. Experimental approaches of adaptive immunity, particularly for T cells, have been the main focus of immunosenescence research. This systematic review evaluates and discusses T cell markers implicated in immunosenescence.Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 69 publications
(371 reference statements)
3
84
0
1
Order By: Relevance
“…CD28 – CD8 + T cells are late-differentiated cells, known to express combinations of NK receptors, such as CD56, NKG2A, and KIRs, as well as inhibitory receptors and markers of terminal differentiation, including PD-1, CD57, and LAG3 ( 45 ). Expression of these inhibitory factors and increasing abundance with age have led to suggestions that these cells have reduced immunostimulatory capacity and are associated with immune senescence ( 46 ). While early studies found reduced proliferative ability compared with CD28 + cells ( 47 ), more recent studies have shown similar proliferative ability between CD28 + and CD28 – CD8 + T cells ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD28 – CD8 + T cells are late-differentiated cells, known to express combinations of NK receptors, such as CD56, NKG2A, and KIRs, as well as inhibitory receptors and markers of terminal differentiation, including PD-1, CD57, and LAG3 ( 45 ). Expression of these inhibitory factors and increasing abundance with age have led to suggestions that these cells have reduced immunostimulatory capacity and are associated with immune senescence ( 46 ). While early studies found reduced proliferative ability compared with CD28 + cells ( 47 ), more recent studies have shown similar proliferative ability between CD28 + and CD28 – CD8 + T cells ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…These changes can be divided into those affecting the abundance of different subpopulations and those influencing the functional capacity of these cells. Concerning the first ones, immunosenescence has been linked to an inverted ratio CD4/CD8 and with the accumulation of T memory cells, among many others, which were recently reviewed [ 47 , 48 , 49 ]. These changes are thought to be the result of the immunological history of the individual and, as such, an adaptation to the circumstances in the old [ 46 ] (i.e., the higher need of T CD8 cytotoxic cells due to increased cancerous cells, or no need to maintain the T naïve cell repertoire, given the little chance of discovering a new antigen at the very old age).…”
Section: Impact Of Immunosenescence In Oxi-inflamm-agingmentioning
confidence: 99%
“…Aging is frequently accompanied by immunosenescence, a reduction in function of the innate and adaptive immune systems [ 190 ]. In particular, a paucity of recent thymocyte emigrants, as well as changes in B cells [ 191 ] and CD4+ and CD8+ T cells [ 191 , 192 ] in patients with MS can compound the immunosuppressive effect of some DMTs [ 193 ]. The well-established safety profile of IFN β DMTs suggests its potential usefulness in older patients, particularly those with comorbidities, the risks of which might be heightened by certain MS therapies.…”
Section: The Role Of Im Ifn β-1a In the Current Ms Therapeutic Landscapementioning
confidence: 99%